Different Development Scenarios to Increase the Production Rates for Fauqi Oil Field Southeastern Iraq - AbdulMajeed, Rwaida Kaiser (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The Fauqi field is located about 50Km North-East Amara town in Missan providence in Iraq. Fauqi field has 1,640 MMbbl STOIIP, which lies partly in Iran. Oil is produced from both Mishrif and Asmari zones. Geologically, the Fauqi anticline straddles the Iraqi/Iranian border and is most probably segmented by several faults. There are several reasons leading to drilling horizontal wells rather than vertical wells. The most important parameter is increasing oil recovery, particularly from thin or tight reservoir permeability. The Fauqi oil field is regarded as a giant field with approximately more than 1 billion barrels of proven reserves, but it has recently experienced low production rate problems in many of its existing wells. This study will concentrate on analyzing the Asmari reservoir as the main production reservoir in this field for an oil gravity of 18 API. While, well (FQ-8) has been selected as a pilot well to verify different development scenarios that could be taken to increase the reservoir production rate. The results show that both drilling lateral sections and performing the stimulation process in some reservoir intervals yield positive results to increase good productivity with different percentages. The lateral sections occasionally gave higher productivity than the stimulation process by (2-3) times.